The electronic invoice as an asset title - De La Cruz Gonzales, Diana (2020)
This article analyze the juridical nature of the negotiable invoice originated by a electronic invoice, in his quality of asset title. This, it will point the relevance that it has for the development of electronic factoring in Peru, and the legal aspects that could be object of a better precision.